On Backlund transformation of Riccati equation method and its application to nonlinear partial differential equations and differential-difference equations - Reham Hassan (Open Journal of Mathematical Sciences, 2020)
In this paper, we investigate the equivalence between the Backlund transformation of Riccati equation method and the extended tanh-function method. It is proved that the two methods are equivalent when applying them to partial differential equations and differential-difference equations. Two examples are introduced to justify our results.